Biomechanical evaluation of customized root implants in alveolar bone: A comparative study with traditional implants and natural teeth. Issue 3 (9th September 2022) - Li, Qing; Zhang, Xinyue; Wang, Chao; Hu, Hongcheng; Tang, Zhihui; Fan, Yubo
Abstract: Purpose: To compare and evaluate density changes in alveolar bones and biomechanical responses including stress/strain distributions around customized root implants (CRIs), traditional implants, and natural teeth. Materials and methods: A three‐dimensional finite element model of the maxillary dentition defect, CRI models, traditional restored implant models, and natural teeth with periodontal tissue models were established. The chewing load of the central incisor, the traditional implant, and the CRI was 100N, and the load direction was inclined by 11° in the sagittal plane. According to the bone remodeling numerical algorithm, the bone mineral density and distribution were calculated and predicted. In addition, animal experiments were performed to verify the feasibility of the implant design. The results of the simulation calculations were compared with animal experimental data in vivo to verify their validity. Results: No significant differences in bone mineral density and stress/strain distribution were found between the CRI and traditional implant models. The animal experimental results (X‐ray images and histological staining) were consistent with the numerical simulated results. Conclusions: CRIs were more similar to traditional implants than to natural teeth in terms of biomechanical and biological evaluation. Considering the convenience of clinical application, this biomechanical evaluation provides basic theoretical support for further applications of CRI.